Innowacyjność w bibliotece – doświadczenia bibliotek europejskich - Czerwińska, Elżbieta; Jańdziak, Anna (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The article discusses the reasons for the decrease in interest in the traditional library. The solutions proposed in the literature of the subject and examples of practical solutions used in European libraries are presented.